Studies on neem (Azadirachta indica A. Juss) in Malaysia - Loke, W.H. (Malaysian Plant Protection Society, 2013)
Neem (Azadirachta indica A. Juss) a native tree of the Indian Sub-continent, can be found in all states of Malaysia. The highest population of trees, over 2500, are found in Penang while Kelantan and Trengganu have the least trees. Most of the trees are planted along road sides as shade/ornamental trees with the rest grown in compounds of houses and Indian temples for medicine/religious purposes. Two flowering-fruiting seasons-a main season with flowering in February-April and fruit ripening in June-August and a minor season with flowering in July-September and fruit ripening in October-December were observed. Six concentrations (1.25, 2.5, 5.0, 10.0, 20.0 and 40.4 percent) of neem oil in acetone were evaluated for contact toxicity against second and third larval instars of Plutella xylostella L. Significant mortalities of both larval stages were observed with neem oil concentrations of 10 percent and above. Although the lower neem oil concentrations appeared to be sublethal with regard to contact toxicity effect, physiological and growth disruptive effects such as retardation of growth (prolonged larva stadia), delayed adult emergence and abnormal adults were observed. The effects were more pronounced in the younger instar. Subsequent treatments of pupae and adults of P. xylostella with neem ooil concentrations of 1.25, 2.5, 5.0, and 10.0 percent showed that pupae were generally not affected by the concentrations tested. However, male and female adult moths treated with 2.5 percent and higher concentrations of neem oil had significantly higher 48-h mortalities and shorter longevities than control adults. Using a leaf disc technique, it was shown that concentrations of neem oil at 1.25 percent and bove deterred feeding of P. xylostella larvae substantially as compared to lower concentrations of neem oil at 1.25 percent and bove deterred feeding of P. xylostella larvae substantially as compared to lower concentrations and control (acetone). Neem oil was also found to possess ovicidal properties. Concentrations above 1.25 percent significantly reduced egg hatch while at 20.0 percent all treated eggs were damaged and did not hatch at all